Assessment of patient and dentist preference between conventional and digital diagnostic waxing - Mocelin, Roberta de Cristina [UNESP]; Penteado, Marcela Moreira [UNESP]; Pierre, Fernanda Zapater [UNESP]; Varela Saraiva, Antonio Carlos [UNESP]; Uemura, Eduardo Shigueyuki [UNESP]; Ferraz da Silva, Joao Mauricio [UNESP] (Quintessence Publishing Co Inc, 2021)
Patient expectations for rehabilitations of a high esthetic standard as well as the demand for fast but efficient care have provided new work perspectives in dentistry. Dentists also have to choose between conventional and digital workflows. The aim of the present randomized restorative trial was to compare diagnostic waxing (DW) performed conventionally with its digital counterpart and to assess the two approaches from the point of view of both patient and dentist. Twenty patients with esthetic complaints were selected to undergo molding processes to obtain conventional study models on the one hand, and intraoral scanning to obtain virtual models on the other. Both the 2D planning and 3D virtual models were sent to the laboratory for the performance of DW. The restorative trial was evaluated by one evaluator dentist, while patient opinion was determined through customized questionnaires. The results show that although 80% of patients rated the digital method to be more convenient in terms of execution time and comfort and indicated that scanning was the most reliable way to obtain an impression, 65% chose the conventional DW for their esthetic restoration after the mock-up tests were performed and analyzed. The evaluating dentist conventional preferred the DW technique in 50% of cases assessed. The conclusion is that although digital technology has its advantages, the final esthetic result does not always meet the expectations and demands of patients and dentists.